The paradox of virtue : Helsinki human rights activism during the Cold War (1975-1995) - De Sutter, Bart (Antwerpen : Universiteit Antwerpen, Faculteit Letteren & Wijsbegeerte Geschiedenis, 1995)
1. Introduction -- 2. The struggle for the US Helsinki Watch (1975-1979) -- 3. The making of the International Helsinki Federation for Human Rights (1979-1982) -- 4. Integrating the IHF in the field of human rights (1982-1988) -- 5. The shift to Europe (1989-1995) -- 6. Conclusion: the paradox of human rights advocacy.
PHD dissertation at the University of Antwerpen, "De paradox van principes. Helsinki mensenrechtenactivisme tijdens de Koude Oorlog (1975-1995). Vol. 1".
Includes bibliography, appendix and indexes.
Keywords: International Helsinki Federation for Human Rights; Helsinki Watch (Organization : U.S.); Human rights advocacy